Postmortem molecular screening in unexplained sudden death - Chugh, Sumeet S; Senashova, Olga; Watts, Allison; Tran, Phuoc T; Zhou, Zhengfeng; Gong, Qiuming; Titus, Jack L; Hayflick, Susan J (Journal of the American College of Cardiology, 2004)
We examined the prevalence of defects in arrhythmia-related candidate genes among patients with unexplained sudden cardiac death (SCD). Patients with unexplained sudden death may constitute up to 5% of overall SCD cases. For such patients, systematic postmortem genetic analysis of archived tissue, using a candidate gene approach, may identify etiologies of SCD. We performed analysis of KCNQ1 (KVLQT1), KCNH2 (HERG), SCN5A, KCNE1,and KCNE2defects in a subgroup of 12 adult subjects with unexplained sudden death, derived from a 13-year, 270-patient autopsy series of SCD. Archived, paraffin-embedded myocardial tissue blocks obtained at the original postmortem examination were the source of deoxyribonucleic acid for genetic analysis. Two patients were found to have the same HERGdefect, a missense mutation in exon 7 (nucleotide change G1681A, coding effect A561T).The mutation was heterozygous in Patient 1, but Patient 2 appeared to be homozygous for the defect. Patch-clamp recordings showed that the A561T mutant channel expressed in human embryonic kidney cells failed to generate HERGcurrent. Western blot analysis implicated a trafficking defect in the protein, resulting in loss of post-translational processing from the immature to the mature form of HERG. No mutations were detected among the remaining four candidate genes. In this autopsy series, only 2 of 12 patients with unexplained sudden death were observed to have a defect in HERGamong five candidate genes tested. It is likely that elucidation of SCD mechanisms in such patients will await the discovery of multiple, novel arrhythmia-causing gene defects.